“I Feel Permanently Traumatized By It”: Physical and Emotional Impacts Reported by Men Forced to Penetrate Women in the United Kingdom - Weare, Siobhan (Journal of interpersonal violence, 2021)
This article reports findings from the first empirical study in the United Kingdom on forced-to-penetrate cases, where a man is forced to penetrate a woman either orally, vaginally, or anally with his penis and without his consent. Using an online survey, data were collected in relation to the physical and emotional impacts experienced by 154 men following their most recent forced-to-penetrate experience. Quantitative and qualitative data were collected through the use of closed and open-ended survey questions, where participants were asked about the context and circumstances of their most recent experience and whether they had suffered any physical injuries. A unipolar scale was used to measure the emotional impact on participants, with an open-ended follow-up question gathering qualitative data. The majority of participants did not report suffering physical injuries, but those that did suffered injuries to their genitalia and upper bodies. Participants most frequently indicated that their most recent forced-to-penetrate experience had had a severe negative emotional impact on them. Negative emotional impacts disclosed by participants were complex, ranging from anxiety and depression, to self-harm and suicidal thoughts and attempts. Quantitative analysis highlighted that when certain variables were present, participants more frequently reported physical injuries, as well as higher average levels of emotional harm. The findings from the study challenge existing understandings of masculinity and rigid sex and gender roles, which assume that men will always consent to sexual activity with a woman and that they cannot or do not experience emotional or physical harms at the hands of a woman. The findings are also considered in relation their implications for law and legal discourse, where evidence of harm is used as a justification for the criminalisation of certain behaviors and the severity of the legal response through sentencing.